Gut Microbiota Modulation to Enhance Exercise Performance and Recovery - Systematic Review - Czarnota, Maksymilian; Ossowska, Weronika; Ösztreicher , Wiktoria (Quality in Sport, 2025)
Background: Recent evidence suggests that the gut microbiota can influence host metabolism, immunity, and tissue repair—processes critical for exercise performance and recovery. Objective: To synthesise human research examining whether modulation of the gut microbiota—via probiotics, prebiotics, diet, or training—affects physical capacity and post-exercise recovery. Methods: A systematic search of PubMed and Scopus (until May 2025) identified peer-reviewed human studies involving gut-directed interventions or athlete comparisons reporting on physical performance, fatigue, immune response, or gut integrity. Thirty-five studies met inclusion criteria and were narratively analysed. Results: Regular endurance or mixed training increased microbial diversity, SCFA-producing taxa, and gut-barrier integrity, while excessive loads reduced diversity and increased permeability. Multi-strain probiotic or synbiotic supplementation (≥10¹⁰ CFU/day, ≥4 weeks) improved endurance, reduced muscle-damage markers, and lowered illness incidence during intense training. Fibre-rich diets enhanced beneficial taxa and reduced inflammation. Conclusions: Modulating the gut microbiota is a promising adjunct to training and nutrition strategies. Periodised probiotic use, sustained fibre intake, and personalised gut-health monitoring may optimise performance and recovery. Further well-designed, long-term trials are needed to clarify causality and refine recommendations.